2022
DOI: 10.1029/2022gl098663
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Climate Change on Midlatitude Subseasonal Prediction Skill Provided by the Tropics

Abstract: Subseasonal timescales (∼2 weeks–2 months) are known for their lack of predictability, however, specific Earth system states known to have a strong influence on these timescales can be harnessed to improve prediction skill (known as “forecasts of opportunity”). As the climate continues warming, it is hypothesized these states may change and consequently, their importance for subseasonal prediction may also be impacted. Here, we examine changes to midlatitude subseasonal prediction skill provided by the tropics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Recent research has shown that the MJO has become and will likely continue to become more predictable in a future climate (Du et al., 2023), which could subsequently improve midlatitude subseasonal skill provided by the MJO. On the other hand, previous research suggests ENSO may be a main tropical driver of future midlatitude subseasonal predictability changes (Mayer & Barnes, 2022). Therefore, future research should explore how our results may change in a future, warmer climate.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent research has shown that the MJO has become and will likely continue to become more predictable in a future climate (Du et al., 2023), which could subsequently improve midlatitude subseasonal skill provided by the MJO. On the other hand, previous research suggests ENSO may be a main tropical driver of future midlatitude subseasonal predictability changes (Mayer & Barnes, 2022). Therefore, future research should explore how our results may change in a future, warmer climate.…”
Section: Discussionmentioning
confidence: 95%
“…Wang & Robertson, 2019). Further, recent work suggests ENSO may play a main role in changes to midlatitude subseasonal predictability in a future, warmer climate (Mayer & Barnes, 2022). While ENSO is often used for seasonal prediction (e.g., Gibson et al, 2021;Winkler et al, 2001), there is also considerable literature that highlights ENSO teleconnections as a driver of midlatitude subseasonal variability, particularly in boreal winter by also modulating the Aleutian Low (e.g., Chapman et al, 2021;Kumar & Hoerling, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neural network approach allows us to make subseasonal predictions without the need for a forecast model. The fields of weather and climate science have benefitted from applications of neural networks to learn physical relationships within the Earth system via explainability techniques (Ham et al 2019, McGovern et al 2019, Toms et al 2020, Antonios et al 2021, Gordon et al 2021, Martin et al 2022, Mayer and Barnes 2022, Straaten et al 2023. Here, we use shallow artificial neural networks (ANNs) to quantify U.S. West Coast subseasonal precipitation skill and identify forecasts of opportunity provided by the tropics within CESM2.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we use the CESM2 historical simulation to train neural networks to quantify the subseasonal prediction skill within CESM2 without the need for a forecast model. The fields of weather and climate science have benefitted from applications of neural networks to learn physical relationships within the Earth system via explainability techniques (Gordon et al, 2021;Ham et al, 2019;Mamalakis et al, 2021;Martin et al, 2022;Mayer & Barnes, 2022;McGovern et al, 2019;Toms et al, 2020;van Straaten et al, 2023). Here, we use shallow artificial neural networks to quantify U.S. West Coast subseasonal precipitation skill and identify forecasts of opportunity provided by the tropics within CESM2.…”
Section: Introductionmentioning
confidence: 99%